Pendampingan Peningkatan Mutu Sistem Manajerial Pada Amal Usaha Muhammadiyah Paciran Kabupaten Lamongan - Maulidyah Amalina Rizqi (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Most universities are more concerned with accreditation or SPME rather than SPMI, accreditation has always been the goal of improving the quality of study programs or universities. Once the accreditation is out, the institution will no longer carry out internal quality evaluations. In the law, the SPMI process must be carried out by universities at least once a year. If study programs or universities only improve their quality in order to achieve good accreditation scores, there is a tendency that internal quality will not increase. The most important thing to achieve good accreditation is to apply the Continuous Quality Improvement (CQI) pattern. By improving the internal quality first, it is certain that the accreditation process will also be good. This service seeks to help the Tarbiyah Muhammadiyah Paciran Lamongan College of Science become a quality university and can compete with other universities. If the quality of the university is maintained, it can attract students to continue their studies at the university. It is hoped that this service activity using the workshop and mentoring method will make STITM Paciran have a management system that is organized according to university standard rules. The service team will provide explanations regarding the national standards of higher education, the ways that STITM partnering can do to achieve perfect quality. If universities can carry out management according to SN Dikti, an organizational culture will also be formed because all activities are carried out in accordance with SN Dikti.